Parental involvement and academic achievement : a case study of grade five Muslim students in Kandy district of Sri Lanka - Razeen, Thajudeen Fawzul (Kulliyyah of Education, International Islamic University Malaysia, 2018)
There is compelling evidence for the positive influence of parental involvement on children's academic achievement. Its benefits are seen across all socio-economic classes. Despite its significance, parental involvement has received negligible attention in Sri Lanka. This qualitative study seeks to establish how parents in the Kandy district of Sri Lanka are involved in their children's education at school and at home. Barriers to their involvement were investigated with view to overcome them for the benefit of primary education in Muslim school pupils. Semi-structured interviews were used in this study, covering five schools. Respondents were selected with the guidance of the school heads. This research finds that parents, teachers and school heads have very limited understanding of parental involvement. They generally think that involvement is confined to activities conducted at school such as the payment of school fees, providing labor for the construction of school buildings, and providing learning materials and volunteer teachers. Most teachers and school heads believe that parents do not have the level of education needed to adequately guide their children's education. However, a few parents believe that their socio-economic status, or lack thereof, should not prevent them from participating in their children's education. They actually indicate useful ways in which they can be involved. Once the barriers to their involvement have been identified, all teachers and parents were willing to learn about how they could overcome said barriers. They believe that the challenges they are facing regarding parental involvement are resolvable. A major finding of this study is that parental involvement is significant at home and at school. The parents went to school to communicate with the class teachers and also they assisted with their children's homework at home. Parents also have high expectations of their children's academic achievement in final scholarship examinations. There is some difference identified in the way parents are involved in the academic work of their children at school. This is due to some causes such as a lack of time, work constrains, lack of parental commitment and lack of awareness on the new educational system. The findings of this study have implications for teachers, the school principals and educational policy makers.